Methods and protocol flow cells: technique used for studying microbial biofilms - Ndejiko, Mohammed Jibrin (Penerbit UTM Press, 2016)
Biofilms are sessile communities of microorganisms growing on material surfaces and embedded in self-accumulated extracellular polymers. A comprehensive analysis of physical, chemical and biological factors including hydrodynamic and nutrient conditions that regulate their formation is required to adequately gain insight to this complex multicellular microbial life style. Reproducible experimental models that consider all the conditions under which they grow and develop also remain a required tool for studying the biofilms. As a result of its ability to create hydrodynamic and nutrient conditions coupled with continuous and non-destructive ability to grow biofilms, flow cell technology has become one of the most recently patronised models used to study microbial biofilms. This article focuses on recent advancements, principles and practical application of flow cell technology to study microbial biofilms.